Jozef Legrand : Global Village + Cultural Commuters Masterplan : Roadbook 97. - Galerie für Zeitgenössische Kunst, Leipzig; Ministerie van de Vlaamse Gemeenschap; Documenta X, Kassel, 1997 (Kassel : documenta, 1997)
Global Village + Cultural Commuters / Global Village / Kultur Pendler ist eine Mediale Kampagne von Jozef Legrand konkretisiert für die Documenta X. Global Village + Cultural Commuters is a project which exists on several different levels, employing visual, audio and textual documentation, publication and process-based artwork.
Documenta X, Kassel, 21. Juni bis 28. September 1997
Duits & Engels
kunstcatalogus
Keywords: Legrand, Jozef